PCBs Contaminantion of Transformer Oil and its Occupational Health and Safety Status in the Kathmandu Valley, Nepal - K.C., Laxman; Devkota, Bhupendra (International Journal of Environment, 2014)
Electrification in Kathmandu valley had started in 1911 and the use of polychlorinated biphenyls (PCBs) probably started since 1940s (Devkota, 2005). This research work was undertaken to find out the degree and extent of PCBs contamination in transformer oil and to explore its impacts on occupational health and safety issues of the workers and on the environment. The research was focused on Distributions Centers of the Nepal Electricity Authority (NEA) in the Kathmandu valley, NEA Lainchaur workshop and welding workshops of the Kathmandu valley. The samples of transformer oil were collected, safely stored and analyzed using L2000DX Chloride Analyzer, PCBs contamination at >50 ppm level was found in 184 distribution transformers with total volume of PCBs contaminated transformer oil to be 67566.3 Kg. The knowledge on impacts of PCBs contaminated transformer oil on human health and environment was better among NEA employees than among employees of welding workshops, though not satisfactory. Due to very low awareness, the workers come in contact with the transformer oil regularly and many health impacts such as eye problems, skin related complication, weakness and respiratory problems might be due to this exposure; however, exact impacts could not be verified scientifically. DOI: http://dx.doi.org/10.3126/ije.v3i4.11727 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page : 12-23